2009
DOI: 10.1007/s11426-009-0132-x
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical degradation of typical halogenated herbicide 2,4-D in drinking water with UV/H2O2/micro-aeration

Abstract: UV/H 2 O 2 /micro-aeration is a newly developed process based on UV/H 2 O 2 . Halogenated pesticide 2,4-dichlorophenoxyacetic acid (2,4-D) photochemical degradation in aqueous solution was studiedunder various solution conditions. The UV intensity, initial 2,4-D concentrations and solution temperature varied from 183.6 to 1048.7 μW·cm −2 , from 59.2 to 300.0 μg·L −1 and from 15 to 30℃, respectively. The concentration of hydrogen peroxide (H 2 O 2 ) and pH ranged from 0 to 50 mg·L −1 and 5 to 9, and different w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 14 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…Among the advanced oxidation processes (AOPs), photocatalytic oxidation has advantages for treating various organic pollutants compared with other technologies. As the classic method, the strong oxidation ability of the UV/H 2 O 2 process for degrading significant amounts of contaminants in water has been extensively investigated 11–15. The hydroxyl radical generated during this process can non‐selectively oxidize a broad range of organic pollutants, and good removal efficiency for certain acid pharmaceuticals was observed when using the UV process 11, 12, 16.…”
Section: Introductionmentioning
confidence: 99%
“…Among the advanced oxidation processes (AOPs), photocatalytic oxidation has advantages for treating various organic pollutants compared with other technologies. As the classic method, the strong oxidation ability of the UV/H 2 O 2 process for degrading significant amounts of contaminants in water has been extensively investigated 11–15. The hydroxyl radical generated during this process can non‐selectively oxidize a broad range of organic pollutants, and good removal efficiency for certain acid pharmaceuticals was observed when using the UV process 11, 12, 16.…”
Section: Introductionmentioning
confidence: 99%
“…Among advanced oxidation processes (AOPs), the photocatalysis oxidation has the advantage on treating various organic pollutants compared with other technologies. As a typical method, the strong oxidation ability of UV/H 2 O 2 process to degrade many organics in water has been extensively investigated 11, 12. Because the hydroxyl radical generated in this process can oxidize a broad range of organic pollutants non‐selectively 13, some investigations on BZF photocatalysis degradation by AOPs have been carried out, such as ozonation process 14, 15, UV process 16, UV/TiO 2 process 17, photo‐Fenton process 9, and pulse radiolysis 7.…”
Section: Introductionmentioning
confidence: 99%
“…Selected organic (e.g., isopropanol) and mineral (e.g., chlorides, CO 3 2− , HCO 3 − ) compounds can stimulate or inhibit the formation of hydroxyl radicals. Chu et al (2004) observed that 2,4-D concentrations in tap water were less reduced in the UV/ H 2 O 2 /micro-aeration system than in distilled and deionized water. Tap water contains Cl − , CO 3 2− , and HCO 3 − ions with high rate constants in the reaction with hydroxyl radicals; therefore, they may compete for hydroxyl radicals at low concentrations of organic compounds.…”
Section: Fe(oh) 3 and Other Insoluble Iron Species Can Bementioning
confidence: 90%
“…The structure and activity of these compounds are similar to those of the natural hormone indole-3 acetic acid (IAA) (auxin) (Roberts et al 1998;Venkov et al 2000;Buss et al 2006;Mithila et al 2011). At higher concentrations, phenoxy acids induce rapid, uncontrolled growth of dicotyledonous plants, which leads to plant death (Holland et al 2002;Chu et al 2004;Cassanego et al 2010;Song 2014;NIPC 2015;Islam et al 2017).…”
Section: Introductionmentioning
confidence: 98%